2019
DOI: 10.4195/nse2018.11.0020
|View full text |Cite
|
Sign up to set email alerts
|

University Science-Based Education Positively Impacts College Student Views of Water Issues

Abstract: Core Ideas This study measured student opinions about water issues. Students participated in a paired‐survey instrument of an environmental science class. tSudent views of water resources were affected by gender and college major. Science‐based education changed preconceived water resource opinions of students. Most students entering universities in the United States have established views on water resource issues. The purpose of this 25‐year study was to measure the impact of science‐based education on stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
2
7
0
1
Order By: Relevance
“…Of our survey respondents, 62% reported that they first considered whether water was safe before drinking it (Table 1). A common misconception among university students is that bottled water is safer to drink than tap water (Mahler, 2019; Saylor et al., 2011), and this may explain why 44% of the students that we surveyed primarily drank bottled water on campus (Table 1). Similarly, 36% of students at West Virginia University regularly drank bottled water (Leveque & Burns, 2018), 44% at Purdue University (Saylor et al., 2011), 47% at the University of South Florida–Tampa (Graydon et al., 2019), and 48% at Hong Kong University (Qian, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of our survey respondents, 62% reported that they first considered whether water was safe before drinking it (Table 1). A common misconception among university students is that bottled water is safer to drink than tap water (Mahler, 2019; Saylor et al., 2011), and this may explain why 44% of the students that we surveyed primarily drank bottled water on campus (Table 1). Similarly, 36% of students at West Virginia University regularly drank bottled water (Leveque & Burns, 2018), 44% at Purdue University (Saylor et al., 2011), 47% at the University of South Florida–Tampa (Graydon et al., 2019), and 48% at Hong Kong University (Qian, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…(2011) found that female college students drank more bottled water and that undergraduates drank more bottled water than graduate students. When assessing what students consider when making decisions about what to drink, many studies (Leveque & Burns, 2018; Mahler, 2019; Qian, 2018; Saylor et al., 2011) point to the impacts of safety perception, organoleptic perception (e.g., taste, odor, color), convenience, family habits, and connections to environmental issues. Saylor et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although less than 40% of students considered over‐population a problem in the United States, gender was found to be an important factor evaluating this environmental issue. Earlier classroom survey work has shown females to be more pessimistic than males about environmental issues including water and energy (Mahler, 2019; Mahler & Barber, 2017).…”
Section: Resultsmentioning
confidence: 99%